Arousal State-Dependent Alterations in VTA-GABAergic Neuronal Activity - Eban-Rothschild, Ada (eNeuro, 2020)
Decades of research have implicated the ventral tegmental area (VTA) in motivation, learning and reward processing. We and others recently demonstrated that it also serves as an important node in sleep/wake regulation. Specifically, VTA-dopaminergic neuron activation is sufficient to drive wakefulness and necessary for the maintenance of wakefulness. However, the role of VTA-GABAergic neurons in arousal regulation is not fully understood. It is still unclear whether VTA-GABAergic neurons predictably alter their activity across arousal states, what is the nature of interactions between VTA-GABAergic activity and cortical oscillations, and how activity in VTA-GABAergic neurons relates to VTA-dopaminergic neurons in the context of sleep/wake regulation. To address these, we simultaneously recorded population activity from VTA subpopulations and electroencephalography/electromyography (EEG/EMG) signals during spontaneous sleep/wake states and in the presence of salient stimuli in freely-behaving mice. We found that VTA-GABAergic neurons exhibit robust arousal-state-dependent alterations in population activity, with high activity and transients during wakefulness and REM sleep. During wakefulness, population activity of VTA-GABAergic neurons, but not VTA-dopaminergic neurons, was positively correlated with EEG γ power and negatively correlated with θ power. During NREM sleep, population activity in both VTA-GABAergic and VTA-dopaminergic neurons negatively correlated with δ, θ, and σ power bands. Salient stimuli, with both positive and negative valence, activated VTA-GABAergic neurons. Together, our data indicate that VTA-GABAergic neurons, like their dopaminergic counterparts, drastically alter their activity across sleep-wake states. Changes in their activity predicts cortical oscillatory patterns reflected in the EEG, which are distinct from EEG spectra associated with dopaminergic neural activity.